Price and volatility transmissions among natural gas, fertilizer, and corn markets: A revisit - Zhengliang Yang; Xiaoxue Du; Liang Lu; Hernan Tejeda (Journal of Risk and Financial Management, 2022)
In this paper, we revisit price and volatility transmission among natural gas, fertilizer, and corn markets; an important issue was explored in previous work. An update of the results is urgently needed due to the recent enormous price volatility in the commodities, fertilizer, and energy markets. We followed the same methodology as previous work and used the vector error correction model and the multivariate generalized autoregressive heteroskedasticity model, but we adopted a new methodology to gather higher frequency data for fertilizer to estimate the interactions and examine the mechanisms between these market prices. Our results are consistent with previous research showing that natural gas price returns in the short-term are significantly affected by its lagged returns from itself and corn markets, and it will be affected by its lagged return sand fertilizer markets. However, we did not find a significant relationship among fertilizer, corn, and natural gas markets from May to November 2021. Moreover, the lagged conditional volatility of corn prices will affect the conditional volatility in the natural gas market but not vice versa.
Keywords: 330; price volatility; transmission mechanism; natural gas; ertilizer; tcorn